2022
DOI: 10.7759/cureus.21169
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Lung Cancer and Sarcoidosis: A Systematic Review

Abstract: Lung cancer has been the leading cause of cancer-associated deaths worldwide. While numerous reasons, including tobacco smoking, may lead to lung cancer, the purpose of this article was to explore the association between sarcoidosis, a multisystem granulomatous disorder, and lung neoplasms. A literature search was done on multiple databases with appropriate keywords, and the authors selected case reports where patients were diagnosed with sarcoidosis and lung cancer. These reports were analyzed in detail, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Since the late 1950s, there has been an ongoing debate on the relationship between SLRs and malignancies, given that sarcoidosis may precede, be diagnosed concurrently with, or follow an oncologic disease [ 5 , 6 ]. Recently, literature has indicated a common etiology in at least 25% of patients [ 8 ]. An analysis of both clinical and radiological features of a series of 29 granulomatosis patients with pre-existing cancer (mainly breast cancer and lymphoma) additionally showed that sarcoidosis following a malignancy is usually indistinguishable from idiopathic sarcoidosis, suggesting that the diagnosis and management of this condition should be further standardized regardless of the cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the late 1950s, there has been an ongoing debate on the relationship between SLRs and malignancies, given that sarcoidosis may precede, be diagnosed concurrently with, or follow an oncologic disease [ 5 , 6 ]. Recently, literature has indicated a common etiology in at least 25% of patients [ 8 ]. An analysis of both clinical and radiological features of a series of 29 granulomatosis patients with pre-existing cancer (mainly breast cancer and lymphoma) additionally showed that sarcoidosis following a malignancy is usually indistinguishable from idiopathic sarcoidosis, suggesting that the diagnosis and management of this condition should be further standardized regardless of the cause.…”
Section: Discussionmentioning
confidence: 99%
“…Second, considering that the efficacy of immunotherapy may be impeded by the addition of systemic steroids to control SLR symptoms, many physicians prefer to hold the ICI [ 11 ]. Finally, avoiding the unnecessary use of immunosuppressive drugs in patients with irAEs is highly recommended [ 8 , 11 ]. It is also essential to consider the potential consequences of stopping anticancer treatment, particularly in the absence of clear management recommendations [ 4 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within this Research Topic, experts in the field have shared their insights, experience, and research data to deepen our understanding of sarcoidosis. In our view, the agenda for future research includes but is not limited to: (1) what does assist us in making a confident diagnosis of sarcoidosis?, (2) the development of disease clustering criteria for clinical trials, (3) a definition of an applicable response index for measuring outcomes in clinical trials, (4) further explore the role of calcium/vitamin D metabolism in sarcoidosis, and ( 5) investigate the molecular mechanisms underlying the pathogenesis of the disease. Specialists from all fields, such as pulmonologists, rheumatologists, dermatologists, and neurologists, among many others, should embrace these challenges to improve the diagnosis and treatment of sarcoidosis patients for whom very few therapeutic options are available.…”
Section: Discussionmentioning
confidence: 99%
“…The first article, written by Tirelli et al describes a case of concurrent adenocarcinoma of the lung and coexistent sarcoidosis, which is rare and therapeutically challenging. A recent systematic review identified nine case reports and highlighted that meticulous diagnostic testing is essential to differentiate metastatic disease from sarcoid or sarcoid-like lesions (1). The following case report by De Cinque et al focuses on testicular sarcoidosis, an exceedingly rare manifestation of sarcoidosis.…”
Section: Learning From Case Reportsmentioning
confidence: 99%
“…LC ranks first among the causes of cancer-related deaths in the world ( 96 ). METTL14 facilitated the maturation of miR-30c-1-3p and mediated the expression of its target gene MARCKSL1 through miR-30c-1-3p to suppress the progression of LC ( 97 ).…”
Section: M6a Modification and Solid Tumorsmentioning
confidence: 99%